Is functional dependence of Duchenne muscular dystrophy patients determinant of the quality of life and burden of their caregivers? - Maria Clara Drummond Soares de Moura; Hanna Camila Wutzki; Mariana Callil Voos; Maria Bernadete Dutra Resende; Umbertina Conti Reed; Renata Hydee Hasue (Arquivos de Neuro-Psiquiatria)
Objective The relationship between functional dependence and quality of life (QOL) in Duchenne muscular dystrophy (DMD) patients and burden and QOL in caregivers is not clear. This study investigated possible relationships between functional dependence/QOL of DMD patients and QOL/burden of caregivers. Method This study included 35 boys (6-17 years) and respective caregivers (above 21 years). Caregivers answered to World Health Organization Quality of Life and Zarit Burden Interview questionnaires. Patients were assessed with the Motor Function Measure and the Autoquestionnaire Qualité de vie Enfant Imagé. Spearman correlations and linear regressions were run to investigate relationships between the variables. Results The occurrence of lower QOL and higher burden among the caregivers of patients with Duchenne muscular dystrophy was evidenced. The functional dependence of patients was not considered a determinant factor. Higher caregivers’ burden was related to lower caregivers’ QOL and to higher patients’ ages.